Integrating European retail payment systems: some economics of SEPA - Kari Kemppainen (Bank of Finland, 2008)
Using a spatial competition model of retail payment networks, this paper discusses the likely economic consequences associated with the formation of the Single Euro Payments Area (SEPA). The model considers an expansion of positive network externalities on the demand side and adjustment cost on the supply side and reveals that the introduction of SEPA may not lead to a fully competitive and integrated retail payment markets. This is especially the case when the markets are segments before the introduction of SEPA. In such a scenario, the post-integrated markets are likely to remain segmented or will be characterised by a kinked equilibrium where no significant price competition takes place. In both outcomes, SEPA leads to increased prices, larger network sizes (ie increased number of customers) and a higher consumer surplus. Additionally, if the SEPA-induced adjustment costs for payment networks are not prohibitively high, SEPA may also lead to an increase in both profits and social welfare.
URN:NBN:fi:bof-20140807387
Keywords: G21; 330; integration; network effects; retail payments